Information, credit and market access by upland tribals in north-eastern Himalaya of India: An empirical study - PANDEY, D K; DE, H K; PHUKAN, B R; MEHRA, T S; MISHRA, B P; CHANU, T M; TOMAR, KRISHNA S (The Indian Journal of Agricultural Sciences, 2018)
The present study was conducted during 2016-17 in Arunachal Pradesh, Manipur, Meghalaya, Mizoram, Nagaland and Tripura states of the North-Eastern Himalayan (NEH) region to analyze the extent of institutional support, viz. information, credit and market access in the tribal dominated districts. Findings of the study reveal that 87.80% respondents owned/use mobile phone, whereas extension contact was found to be very poor in the study area as a whole. Awareness and usage of formal information sources reveal that about one fourth (24%) were aware of Indian Council of Agricultural Research (ICAR) centres, whereas only 17.6% respondents were aware of Krishi Vigyan Kendra and Agricultural University/line department. Access to these institutions was found to be poor owing to poor connectivity and remoteness of the area. About 43% respondents had no access to institutional credit, whereas informal sources of rural credit account for about 21.8% of the loan volume to tribal households and kins/relatives (41.4%) were the largest source of informal credit. Marketing and associated infrastructure were identified as major determinants of their livelihood diversification.